Kilka uwag dotyczących wzmacniania skali pomiaru przy obliczaniu odległości - Pawełek, Barbara (Some Remarks about Strengthen of Scale of Measurement at Calculation of Distance, 2007)
In comparative analysis into complex economic phenomena to assessment of similarity of objects uses itself for example measures of distance. In the paper were presented some consequences of strengthen of interval scale. This problem appears among others at applying to measurements on interval scale the modified distance measures for measured data on quotient scale.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 236-244